Health Leadership Lessons From a Fine Detective - Dinesh Arya (ACHSM, 2020)
Objective: To explore lessons on leadership from interactions and success of two very fine detectives - Sherlock Holmes and Dr. Watson  Methods: From the review of Sir Arthur Conan Doyle's depiction of Sherlock Holmes, some clear and useful lessons have been drawn for health leaders. An erratic, unsystematic Sherlock Holmes and an analytical, systematic and introspective Dr. Watson provide useful lessons for health leaders on trust, teamwork and how complementary abilities enable the achievement of a great outcome.  Conclusions: It is really important for health leaders to not forget the elementary message to remain focused on care provision, enable the provision of care that the community wishes to receive and avoid of the temptation of making decisions without appropriate information set to inform those decisions.